Why is there a home bias? An analysis of foreign portfolio equity ownership in Japan - Kang, Jun-Koo; Stulz, Rene´M. (Journal of Financial Economics, 1997)
This paper studies stock ownership in Japanese firms by non-Japanese investors from 1975 to 1991. Existing models predicting that foreign investors hold national market portfolios or portfolios tilted towards stocks with high expected returns are inconsistent with our evidence. We document that foreign investors hold disproportionately more shares of firms in manufacturing industries, large firms, and firms with good accounting performance, low unsystematic risk, and low leverage. Controlling for size, there is evidence that small firms that export more firms with greater share turnover, and firms that have ADRs have greater foreign ownership.